The impact of time between surgery and adjuvant chemoradiotherapy in advanced oral cavity squamous cell carcinoma - Mrosk, Friedrich; Absah, Majd; Richter, Maximilian; Sprünken, Erin; Doll, Christian; Kreutzer, Kilian; Rendenbach, Carsten; Beck, Marcus; Klinghammer, Konrad; Heiland, Max; Koerdt, Steffen (Frontiers in Oncology, 2024)
Objective: In advanced oral squamous cell carcinoma (OSCC), adjuvant therapy (AT) is an important part of the treatment to ensure extended locoregional control after primary surgical resection. The impact of the time interval between surgery and AT on the oncological prognosis remains unclear, particularly in high-risk constellations. The aim of this study is to categorize treatment delays and to determine their impact on the oncological prognosis within the context of the histopathological risk parameters of patients with advanced OSCC.In this single-institutional retrospective cohort study, all patients treated for OSCC between 2016 and 2021 and who received postoperative chemoradiation (POCRT) were included.Patients were divided into two groups: Group I: ≤ 6 weeks between surgery and POCRT; and Group II: > 6 weeks between surgery and POCRT.Results: Overall, 202 patients were included (Group I: 156 (77.2%) vs. Group II: 46 (22.8%)). There were no statistically significant differences in epidemiological aspects and histopathological risk factors between the two groups. The maximum time to initiation of POCRT was 11 weeks. Delayed POCRT initiation had no statistically significant influence on the 5-year OS (61.6% vs. 57.3%, p = 0.89), locoregional control rate (38.6% vs. 43.3%, p = 0.57), and RFS (32.3% vs. 30.4%, p = 0.21).